Rib stress fractures in elite rowers. A case series and proposed mechanism - Karlson, K. A. (The American Journal of Sports Medicine, 1998)
The potential cause of stress fractures of the rib in elite rowers was examined by a retrospective review of 14 fractures in 10 patients. Fractures occurred on the antero- to posterolateral aspects of ribs 5 through 9 and were most often associated with long-distance training and heavy load per stroke. A review of the literature yields striking similarities between these stress fractures and fractures caused by cough. It is suggested that actions of the serratus anterior and external oblique muscles on the rib cause stress fracture because of the repetitive bending forces in both rowing and coughing. A technique involving less use of both muscles through a truncated arm pull-through and a decreased layback position at the end of the stroke, and equipment changes to decrease length of the lever arm, should yield a decreased risk of rib stress fractures in rowing.